Living with Bats: The Case of Ve Golokuati Township in the Volta Region of Ghana - Ayivor, J.S.; Ohemeng, F.; Tweneboah Lawson, E.; Waldman, L.; Leach, M.; Ntiamoa-Baidu, Y. (Journal of Environmental and Public Health, 2017)
Ayivor, J.S., Institute for Environment and Sanitation Studies (IESS), College of Basic and Applied Sciences, University of Ghana, P.O. Box LG 209, Legon, Accra, Ghana; Ohemeng, F., Department of Sociology, School of Social Sciences, College of Humanities, University of Ghana, P.O. Box LG 72, Legon, Accra, Ghana; Tweneboah Lawson, E., Institute for Environment and Sanitation Studies (IESS), College of Basic and Applied Sciences, University of Ghana, P.O. Box LG 209, Legon, Accra, Ghana; Waldman, L., Institute of Development Studies, University of Sussex, Brighton, United Kingdom; Leach, M., Institute of Development Studies, University of Sussex, Brighton, United Kingdom; Ntiamoa-Baidu, Y., Department of Animal Biology and Conservation Science, College of Basic and Applied Sciences, University of Ghana, Legon, Accra, Ghana, Centre for African Wetlands, University of Ghana, P.O. Box LG 67, Legon, Accra, Ghana
Keywords: Bats; Ve Golokuati Township; Volta Region; Ghana; zoonotic pathogens; Epomophorus gambianus roost